Sosialisasi Bahaya Rokok Untuk Meningkatkan Kesadaran Masyarakat Terhadap Dampak Rokok Bagi Kesehatan Di Desa Kuta Tuha Kecamatan Panga Kabupaten Aceh Jaya - Srie Wahyuni; Cut Rahmi Muharrina; Saufa Yarah; Qurananayati Qurananayati; Erna Erna (Jurnal Pengabdian Masyarakat, 2025)
Smoking is still a serious social problem in Indonesia. Based on data from the Ministry of Health, the prevalence of active smokers continues to increase, not only among adults but also among teenagers, even though the dangers of smoking have been scientifically proven and can have long-term impacts on both active and passive smokers. In response to this phenomenon, this community service activity carries out outreach with the aim of raising awareness among the community in an effort to resolve the smoking problem in Desa Kuta Tuha kecamatan Panga, Kabupaten Aceh Jaya. The methods used in this activity are interactive counseling, question and answer discussions and simulations of how to refuse invitations to smoke. From the results of the activity, it was found that most participants showed an increased understanding of the dangers of smoking. Some participants even committed to reducing their smoking habit. The Community Service program was well-conducted, and after the outreach, there was a noticeable increase in knowledge. Therefore, this Community Service program is an important way to foster social awareness by avoiding smoking. This education on the dangers of smoking is not only about conveying information, but also building collective awareness that a healthy life is everyone's right.